Heart Rate Variability: A Psychophysiological Factor Related to Both Regular Physical Activity and Eudaimonic Well‐Being Among Young Adults - Yoshino Murakami; Daisuke Goto; Hayato Tsukamoto; Kazuho Yamaura; Takeshi Hashimoto (Brain and Behavior)
ABSTRACT Introduction Eudaimonic well‐being (EWB), which refers to optimal human functioning, is associated with psychophysiological outcomes, such as reduced inflammation and a lower risk of depression. Although physical activity (PA) and mindfulness have been shown to be predictive factors for EWB, potential mediators of the relationships of PA or mindfulness with EWB have yet to be identified. PA, mindfulness‐related psychophysiological factors (including serotonin [5‐HT], oxytocin [OXT]), and dopamine [DA] levels), and heart rate variability (HRV) have been shown to be associated with mental disorders or emotion regulation capacity. Purpose The purpose of this study is to explore the potential psychophysiological factors associated with PA, mindfulness and EWB. Methods A total of 49 young adults (25 males, 24 females) were included with an average age of 25 years (± 5). Plasma 5‐HT, OXT, and DA levels were obtained via blood samples from the brachial vein and were analyzed with enzyme‐linked immunosorbent assays (ELISAs), and HRV was obtained via 5‐min electrocardiograms (ECGs), with participants in the supine position. Spearman's correlation analyses were performed, followed by partial correlation analyses controlling for age, sex, and social status (i.e., student or working professional). Results HRV was found to be positively correlated with both moderate‐intensity PA (r = 0.47, p = 0.04) and EWB (purpose in life; r = 0.50, p = 0.03), even after controlling for relevant variables. On the other hand, neither 5‐HT, OXT, nor DA was correlated with PA, mindfulness, and EWB. Conclusion These results suggest that HRV may mediate the relationship between PA and EWB. Additional intervention studies are needed to elucidate the causal relationships among PA, HRV, and EWB.